Role and occupation of women in ancient Kurdistan (in the third millennium BC from the mirror of archaeology) - Reza, Hazha Abdul Jabbar (Sulaimani Journal for Humanities, 2026)
There is no doubt that women as an important individual in society in general and the family in particular have played a great role since ancient times. In this study, we will shed light on the appearance of women on the archaeological sites of Kurdistan in the third millennium BC. In addition, in the light of the cuneiform texts, we learn about the personal names, duties and occupations of some of the women who appear on the monuments (such as the tubular seals) of this millennium Queen Uqnitum and wife Uqnitum Dam appear in two different roles, the first as the queen of the country, the second as the king's main wife and mother of the crown prince, and the name Zamena as the right-hand man The queen's assistant, her personal attendant, and her children's mother, Tuli, appear as Uqnitum's cook. They served the Queen as two important figures in the royal palace and carried out their duties such as preparing the daily meals of Queen Oqnitum and conducting special meals for celebrations.
Keywords: Uqnitumthe queen; Uqnitum the wife; Zamena Zamena ʽ the mother; ʼTuli Tuli the cook; the potter; the servant